P359 Influence of the nature of immunosuppressive therapy in patients with inflammatory bowel diseases on the level of immunoglobulins G after a Coronavirus Infection. (27th May 2021) - Knyazev, O; Kagramanova, A; Lishchinskaya, A; Noskova, K; Chernova, M; Shkurko, T; Veselov, A; Kulakov, D; Li, I; Parfenov, A
Abstract: Background: Currently, there are differences in the results of international studies and treatment outcomes in patients with inflammatory bowel disease (IBD) and COVID-19. Further research is needed to help answer the questions: do IBD patients have an increased risk of contracting SARS-CoV-2? Do IBD patients have more severe COVID-19 outcomes? Does IBD therapy increase the risk of infection? Do any IBD treatments protect against COVID-19? Objective: To study the effect of immunosuppressors, genetically engineered biologics, and janus kinase blockers on the level of SARS-CoV-2 class G immunoglobulins in IBD patients who underwent COVID-19. . Methods: The level of SARS-CoV-2 class G immunoglobulins was analyzed in 66 patients with IBD after COVID-19 infection. Male 28 (42.4%) of women 38 (57.6 per cent). The median age was 39±4.2 years. The duration of the anamnesis ranged from 1 to 8 years (Iu 4 years). The patients were divided into two groups, depending on the therapy performed: Group 1 (n=31) received long-term (more than 1 year) immunosuppressants (azathioprine/6-mercaptopurine/tofacitinib), group 2 (n=35) received anti-TNF-α therapy. The level of SARS-CoV-2 class G immunoglobulins was determined by the immunochemiluminescence method. Results: After 4-6 weeks later, after a twice negative smear of PCR from the nose and oropharynx for SARS-CoV-2, in patients (n=31) receiving anti-relapse therapy with systemic IBD (azathioprine/6-mercaptopurine) and selective (tofacitinib) immunosuppressants, the average level of Ig G was 44.1±9.8 U/l. Among patients with IBD receiving anti-TNF-a drugs (n=35), the average level of class G immunoglobulins was 133.6±14.4 U/l. The difference was statistically significant (p=0.000003). Conclusion: The level of class G immunoglobulins 3-4 weeks after the COVID-19 infection was significantly higher in IBD patients who received anti-TNF-α drugs.